The effects of mulch from selected multipurpose trees on nitrogen nutrition, growth and yield of maize (Zea mays) - Kamara, A.Y.; Akobundu, I.O.; Sanginga, N.; Jutzi, S.C. (Wiley, 2000)
Leaf extracts and mulch from 14 multipurpose trees were used to test their effects on maize germination, growth and yield. Maize germination was significantly reduced by leaf extracts of all species with increasing extract concentration. The most drastic reductions were caused by Gliricidia sepium, Tetrapleura tetraptera, Lonchocarpus sireceus, Senna siamea and Leucaena leucocephala. Terminalia superba, Tetrapleura tetraptera, Pithecelobium dulce, Gliricidia sepium and Senna siamea significantly reduced maize root growth at the lowest extract concentration, while shoot length was most significantly reduced by Gliricidia sepium, Leucaena leucocephala, Alchornea coordifolia, Pithecelobium dulce, Terminalia superba, and Tetrapleura tetraptera at all concentrations. Growth of maize in pots and yield in the field were controlled by nitrogen supply and uptake. Fast‐decomposing leaf material rich in nitrogen promoted growth and yield of maize. Thus Leucaena leucocephala and Gliricidia sepium, both nitrogen‐fixing legumes with high nitrogen contents and fast‐decomposing leaf materials, significantly increased maize growth and yield. This suggests that the negative effects of leaf extracts observed in the laboratory are ecologically irrelevant in the field.